Empirical Study Of Greenwashing Antecendent And Its Consequences On The Purchase Intention Of Environmental Friendly Products - Muhammad Yusuf As-Shiddiqie; Weni Novandari; MD Aolywlah (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2023)
This study aims to examine the phenomenon of alleged greenwashing at PT Tirta Fresindo Jaya as the producer of Le Minerale bottled water with variables recommended in several previous studies, including Greenwashing, Skepticism, Confusion, Information and Knowledge, and Green Purchase Intention. The population in this research were the people of Central Java who know Le Minerale's disposable gallon products. The sample in this research was 233 respondents who were taken using a purpose random sampling method. Results of research conducted using Structural Equation Modeling (SEM) processed with AMOS software, it shows that: (1) Greenwashing has a significant positive effect on skepticism. (2) Greenwashing has a significant positive effect on Confusion. (3) Skepticism has no effect on green purchase intention. (4) Confusion has no effect on green purchase intention. (5) Skepticism does not mediate the effect of greenwashing on the green purchase intention. (6) Confusion does not mediate the effect of greenwashing on the green purchase intention. (7) Information and knowledge do not moderate the relationship of confusion to the green purchase intention.